Power need of an implement for removing polymer residues from the soil surface in Kazakh horticulture - Adilkhan Niyazbayev; Francesco Garbati Pegna; Kanat Khazimov; Erik Umbetov; Kulmuhanbet Akhmetov; Zhadyra Sagyndykova; Marat Khazimov (Journal of Agricultural Engineering, 2022)
Polymeric materials are largely used in horticulture for mulching and irrigation, but their long degradation time causes various environmental and agronomic problems, hence should be removed at the end of the crop cycle. Among different mechanized techniques for collecting polymer residues from the field, the single-phase one is the most effective, since the plastic film and irrigation tape lifting, cleaning, and collection operations are done in a single pass, though, in most cases, the implements used in Kazakhstan still need an operator to manage the winding mechanism.